AB0288 Safety, effectiveness, work and household productivity of anti-tnf alpha therapy with certolizumab pegol observed in adult rheumatoid arthritis patients in daily practice in canada: first interim analysis of the non-interventional fast can study. (23rd January 2014) - Shaikh, S.; Bensen, W. G.; Chow, A.; Dixit, S.; Fortin, I.; Haraoui, B.; Marina, R. B.; Kayhan, C.; Little, K.; Purcaru, O.; Bessette, L.
Abstract : Background: Certolizumab pegol (CZP), a PEGylated Fc-free anti-TNF, has demonstrated a fast response and acceptable safety profile in rheumatoid arthritis (RA). Objectives: To evaluate the effectiveness and safety of CZP in daily clinical practice in Canada. Methods: FasT CAN is an open-label, multicenter, observational, non-interventional study in patients (pts) eligible to receive CZP per provincial guidelines. Primary endpoint is DAS28 remission (DAS28<2.6) after 2yrs in adult RA pts. The same test (CRP or ESR) was used to calculate change from baseline (BL) DAS28 for each pt based on which test was more prevalent. Other endpoints include pt's assessment of physical function and pain, clinical disease activity index (CDAI) and paid work and household productivity. At the cut-off date (Jan 2012) for this pre-determined interim analysis of data up to Wk20/24, 150 pts had received ≥1 CZP dose. 113 pts were included in the Full Analysis Set (FAS), defined as pts who received ≥1 CZP dose, BL DAS28 >2.6 and ≥1 valid post-BL DAS28 value. Productivity at work and within household was assessed using the validated arthritis-specific Work Productivity Survey. 1 Results: Of 150 pts enrolled, 64.0% reached Wk20/24, 11.3% had not yet reached Wk20/24 and 24.7% had discontinued. Mean age is 55.5yrs, 82.7% are female, median disease duration is 5.5yrs and 64 pts (42.7%) have prior/concomitant biologic exposure. Disease activity and HAQ-DI scores at BL, Wk12 and Wk20/24 are presented in the Table . Of 113 FAS pts, at BL 37.2% were employed and 19.5% were arthritis work disabled. At Wk20/24, employed pts reported fewer workdays lost (mean days/month 1.0 [N=32] vs 1.7 [N=42] at BL) and fewer workdays with productivity reduced by ≥0.5 due to arthritis (mean days/month 1.1 vs 7.0 at BL). Greater improvements in household work productivity were also reported at Wk20/24, with on average 1.5 to 3.1 fold gains in household productivity vs BL. Among all 150 pts, 46/150 (30.7%) reported adverse events (AEs), with infections most frequent (17/150, 11.3%). 2/150 (1.3%) pts reported serious AEs including 1/150 (0.7%) serious infections. There were no deaths. Conclusions: In daily practice in Canada, CZP-treated RA pts achieved rapid improvements in DAS28 remission and physical function by Wk12, sustained to Wk20/24. CZP also improved workplace and household productivity. AE incidence and severity were consistent with previous reports. References: Osterhaus J. Arth Res Ther 2009;11(3):R73. Acknowledgements: The authors acknowledge Costello Medical Consulting for writing and editorial assistance which was funded by UCB Pharma. Disclosure of Interest: S. Shaikh Consultant for: Abbott, Amgen, Johnson and Johnson, Novartis and UCB Pharma, W. Bensen Grant/research support from: Abbott, Amgen, AstraZeneca, BMS, Janssen, Pfizer, Roche, UCB Pharma and Warner Chilcott, Consultant for: Abbott, Amgen, AstraZeneca, BMS, Janssen, Pfizer, Roche, UCB Pharma and Warner Chilcott, Speakers bureau: Abbott, Amgen, AstraZeneca, BMS, Janssen, Pfizer, Roche, UCB Pharma and Warner Chilcott, A. Chow Grant/research support from: Abbott, Amgen, AstraZeneca, BMS, Celegene, Janssen, Lilly, Pfizer, Roche and UCB Pharma, Speakers bureau: Abbott, Amgen, AstraZeneca, BMS, Celegene, Janssen, Lilly, Pfizer, Roche and UCB Pharma, S. Dixit Grant/research support from: UCB Pharma, I. Fortin Consultant for: Abbott, Amgen, AstraZeneca, BMS, Janssen, Lilly, Merck, Novartis, Pfizer, Roche, Takaeda and UCB Pharma, B. Haraoui Grant/research support from: Abbott, Amgen, BMS, Janssen, Pfizer, Roche and UCB Pharma, Consultant for: Abbott, Amgen, BMS, Janssen, Pfizer, Roche and UCB Pharma, Speakers bureau: Abbott, Amgen, BMS, Janssen, Pfizer, Roche and UCB Pharma, R. Marina Employee of: UCB Pharma, C. Kayhan Employee of: UCB Pharma, K. Little Employee of: UCB Pharma, O. Purcaru Employee of: UCB Pharma, L. Bessette Grant/research support from: UCB Pharma, Consultant for: UCB Pharma, Speakers bureau: UCB Pharma